2012
DOI: 10.1002/hep.25544
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after liver transplantation for alcoholic hepatitis are similar to alcoholic cirrhosis: Exploratory analysis from the UNOS database

Abstract: Data on liver transplantation for patients with alcoholic hepatitis are limited. Using the United Network for Organ Sharing database (2004)(2005)(2006)(2007)(2008)(2009)(2010), adults undergoing liver transplantation for a listing diagnosis of alcoholic hepatitis were matched for age, gender, ethnicity, and model for endstage disease (MELD) score, donor risk index, and year of transplantation with three patients transplanted for a listing diagnosis of alcoholic cirrhosis. Study outcomes of graft and patient su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
121
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(125 citation statements)
references
References 25 publications
2
121
0
2
Order By: Relevance
“…The overall recidivism rate with relapse was 12%, with no case of alcoholic relapse within the initial six-month follow-up period after LT. Similar survival rates were reported in a retrospective study comparing LT outcomes for patients with alcoholic hepatitis to those with alcoholic cirrhosis (one year: 93% vs 88%; two years: 91% vs 84%; five years: 80% vs 78%) [48] . However, both studies mentioned an observable difference in society's readiness towards transplants for ALD and other self-inflicted liver diseases, despite their comparable mortality.…”
Section: Concerns On Lt For Acute Alcoholic Hepatitis Without An Abstsupporting
confidence: 81%
See 1 more Smart Citation
“…The overall recidivism rate with relapse was 12%, with no case of alcoholic relapse within the initial six-month follow-up period after LT. Similar survival rates were reported in a retrospective study comparing LT outcomes for patients with alcoholic hepatitis to those with alcoholic cirrhosis (one year: 93% vs 88%; two years: 91% vs 84%; five years: 80% vs 78%) [48] . However, both studies mentioned an observable difference in society's readiness towards transplants for ALD and other self-inflicted liver diseases, despite their comparable mortality.…”
Section: Concerns On Lt For Acute Alcoholic Hepatitis Without An Abstsupporting
confidence: 81%
“…Medical treatment including the use of corticosteroids and/or pentoxifylline reduces the mortality rate to approximately 20%-30% [43,47] . Non-responsive patients suffer high mortality, and thus LT for alcohol hepatitis has been proposed in select patients [35,47,48] . However, alcoholic hepatitis is a controversial indication, or even a contraindication, for LT in most institutions [49,50] due to the high potential for alcohol recidivism, and conceivably due to the lack of pre-transplant abstinence period.…”
Section: Concerns On Lt For Acute Alcoholic Hepatitis Without An Abstmentioning
confidence: 99%
“…Three patients resumed drinking alcohol (at 720, 740, and 1140 days) after transplantation. 18 Singal et al reviewed the United Network for Organ Sharing database from 2004 to 2010 and found 130 patients who had alcoholic hepatitis and had been ''listed'' for transplantation, of whom 59 received a transplant, 40 11 had histologic appearances of alcoholic hepatitis on explant pathology, 33 had cirrhosis, and the remainder had other diagnoses. The graft and patient survivals were similar in the alcoholic hepatitis cohort compared to a control cohort of nonalcoholic recipients, which was selected by sequential matching according to gender, ethnicity, year of transplant, age (AE5 years), donor risk index, and MELD score (AE5 points).…”
Section: Liver Transplant For Alcoholic Hepatitismentioning
confidence: 99%
“…The graft and patient survivals were similar in the alcoholic hepatitis cohort compared to a control cohort of nonalcoholic recipients, which was selected by sequential matching according to gender, ethnicity, year of transplant, age (AE5 years), donor risk index, and MELD score (AE5 points). 40 Wells et al 41 retrospectively reviewed the explanted livers of 148 patients transplanted for ALD alone, drawn from a single-center cohort of 1097 patients transplanted over a period of 18 years. The histological features of alcoholic hepatitis were found in 32 (22%) patients.…”
Section: Liver Transplant For Alcoholic Hepatitismentioning
confidence: 99%
“…However, these data need confirmation in larger prospective studies before implementing this into routine clinical practice. 18,19 Alcohol-related liver disease remains an important public health problem. The World Health Organization's goal is to reduce the mortality rate from alcoholic cirrhosis to below 3.2 per 100,000 population by the year 2020, yet we are far away from this number.…”
mentioning
confidence: 99%